Mendidik Anak Menurut Ajaran Rasulullah: Kajian Hadis Tematik - Muhammad Mahfud; Muhammad Arifuddin (FATAWA: Jurnal Pendidikan Agama Islam, 2022)
Raising children is not an easy thing. However, the Prophet with various methods in teaching knowledge to his friends has provided guidelines on how to educate children in accordance with religious teachings and the demands of the times. This paper aims to explore the traditions about how to educate children according to the teachings of the Prophet. The method used is the maudhu'i (thematic) method. Tracing the hadith using the help of the Miftah Kunuz al-Sunnah book. The results showed that the Prophet taught how to educate children with love. Educational materials are also presented in a hierarchical manner starting with the cultivation of monotheism, instilling a sense of love for the Apostle and his family and reading the Koran, then planting commendable morals, and instilling a spirit of independence in children so that later they become human beings who survive in the world and the hereafter.